Geronimo's Valentine - Geronimo Stilton & Elisabetta Dami
Enter the world of Geronimo Stilton, where another funny adventure is always right around the corner. Each book is a fast-paced adventure with lively art and a unique format kids 7-10 will love. Okay, I'll admit it: I'm a bit of a cheesy mouse from time to time. What can I say? I'm a romantic! That's why Valentine's Day is one of my favorite holidays. This year I had a date with a very special rodent-- Petunia Pretty Paws! But then I got a call from my private investigator friend Hercule Poirat. He had a mystery to solve, and he desperately needed my help. The most beloved, romantic, and famous painting in New Mouse City had been stolen! Now I had to help Hercule AND impress Petunia at the same time. Holey swiss cheese, what was a gentlemouse to do?